2022
DOI: 10.1007/s10549-021-06460-9
|View full text |Cite
|
Sign up to set email alerts
|

A tool to predict disparities in the timeliness of surgical treatment for breast cancer patients in the USA

Abstract: Purpose Breast cancer outcomes are impaired by both delays and disparities in treatment. This study was performed to assess their relationship and to provide a tool to predict patient socioeconomic factors associated with risk for delay. Methods The National Cancer Database was reviewed between 2004 and 2017 for patients with non-metastatic breast cancer managed with upfront surgery. Times to treatment were measured from the date of diagnosis. Patient, tumor, and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…We hypothesize that social determinants of health, represented by surrogate measures such as lower insurance status and neighborhood income, may negatively affect access to care and thus result in longer times to surgery. These findings are consistent with other studies reporting socioeconomic disadvantage to be associated with longer times to surgery . Verdone et al studied the NCDB to generate a nomogram for increased risk for surgical delay of greater than 60 days based on socioeconomic risk factors and found that Medicaid coverage was associated with increased risk of delay compared with private insurance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We hypothesize that social determinants of health, represented by surrogate measures such as lower insurance status and neighborhood income, may negatively affect access to care and thus result in longer times to surgery. These findings are consistent with other studies reporting socioeconomic disadvantage to be associated with longer times to surgery . Verdone et al studied the NCDB to generate a nomogram for increased risk for surgical delay of greater than 60 days based on socioeconomic risk factors and found that Medicaid coverage was associated with increased risk of delay compared with private insurance.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with other studies reporting socioeconomic disadvantage to be associated with longer times to surgery . Verdone et al studied the NCDB to generate a nomogram for increased risk for surgical delay of greater than 60 days based on socioeconomic risk factors and found that Medicaid coverage was associated with increased risk of delay compared with private insurance. Looking at Medicaid expansion, Obeng-Gyasi et al found that although the Affordable Care Act expansion increased breast conservation and reconstruction in Ohio, no difference in time to surgery was observed between those patients without insurance compared with those with Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…35 Individual sociodemographics certainly predict the risk of treatment delays at the patient level. 36 However, it is notable that in our study, adjustment for…”
Section: Discussionmentioning
confidence: 51%
“…Disparities in the quality of cancer care, whether by race or geography, are often attributed to the sociodemographic characteristics of marginalized patient populations, and it is common practice to include risk adjustment for sociodemographic characteristics in outcome‐based oncology quality measures 35 . Individual sociodemographics certainly predict the risk of treatment delays at the patient level 36 . However, it is notable that in our study, adjustment for patient‐level characteristics did not attenuate the observed geographic differences in treatment timeliness for either racial group.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Our findings suggest that machine learning models can similarly be used to identify patients at risk of treatment delays and builds on our prior work in socioeconomically disadvantaged groups. 32 Our model selected neighborhood-level SDOH variables, which are not routinely available in the EHR as variables. However, their contribution to model performance is limited.…”
Section: Discussionmentioning
confidence: 99%